Non-specific cholinesterase activity in mouse spinal ganglia. The usefulness of histochemical study and image analysis for simple characterization of neuron subclasses - Dubovy, P; Svizenska, I; Vega, J A (Cellular and molecular biology, 1990)
Non-specific cholinesterase (ChE) activity was studied histochemically at light and electron microscopical levels in dorsal root ganglia (DRG) of adult mice. The reaction staining and diameter of neuron cells perykaria were measured by using an image analysis system. The methodological approach enable to distinguish 8 subclasses of primary sensory neurons. The proportion of individual subclasses was mapping in three subsequent cervical, thoracal and lumbar DRG. The populations of small-sized neurons increased towards lumbar level similarly as medium and small neurons exhibiting high ChE reactivity. The variations in ChE-containing neurons among DRG from different area may reflect differences in modality-specific primary sensory neurons at each spinal cord level. In addition, the effect of 3 week sciatic nerve transection on the percentage of the subclasses in L4-L6 DRG has been investigated. The number of large neurons was reduced and a decrease of ChE reactivity in medium-size neurons was found in DRG on the operated side. Thus, the present results demonstrate a selective affectation of primary sensory neurons in mouse DRG by the peripheral nerve transection. Different amounts of the reaction product corresponding with ChE activity were found in the nuclear envelope and the cisternae of rough endoplasmic reticulum.
Keywords: cholinesterasy; Mice; Female; Histocytochemistry; elektronová mikroskopie; neurony aferentní; Animals; ženské pohlaví; histocytochemie; spinální ganglia; mužské pohlaví; Cholinesterases; Male; Ganglia, Spinal; zvířata; Microscopy, Electron; myši; Neurons, Afferent